1990
DOI: 10.1002/1097-0142(19900801)66:3<515::aid-cncr2820660319>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Autologous bone marrow transplantation and factor xii, factor vii, and protein c deficiencies report of a new association and its possible relationship to endothelial cell injury

Abstract: Four patients who underwent treatment with high-dose chemotherapy (HDC) and autologous bone marrow transplantation (ABMT) and in whom posttreatment deficiencies of Factor XII and protein C subsequently developed are reported. Factor VII or Factor X deficiencies also developed in several of these patients. Three of these patients experienced chemotherapy-related cardiac, hepatic, or pulmonary toxicity. It is believed by many that endothelial cell injury may be the underlying lesion responsible for these various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…24 We also evaluated basic coagulation parameters and confirmed that most patients have normal baseline levels of INR and PTT, and mildly elevated fibrinogen, reflecting hospitalized population. 25 Conlan et al and others had reported low antithrombin III and protein C levels in AHCT patients 1, 26 , while increased von Willebrand factor and platelet adhesion may also play a role. 6 Presence of inherited thrombophilia was rare and its contribution is difficult to assess.…”
Section: Discussionmentioning
confidence: 96%
“…24 We also evaluated basic coagulation parameters and confirmed that most patients have normal baseline levels of INR and PTT, and mildly elevated fibrinogen, reflecting hospitalized population. 25 Conlan et al and others had reported low antithrombin III and protein C levels in AHCT patients 1, 26 , while increased von Willebrand factor and platelet adhesion may also play a role. 6 Presence of inherited thrombophilia was rare and its contribution is difficult to assess.…”
Section: Discussionmentioning
confidence: 96%
“…12 HSCT recipients have several identifiable risk factors for thrombosis including malignancy, high-dose myeloablative chemotherapy and immune-modulatory drugs, [13][14][15][16] graft versus host disease (GVHD), [17][18][19] infections, 14,20 indwelling vascular catheters and prolonged immobilization. 14 HSCT is also associated with an 'acquired hypercoagulable state' characterized by inflammation, endothelial damage and activation of endothelium-dependent coagulation factors, increase in von Willebrand factor and platelet adhesion, increased thrombin generation, decreased anti-thrombin levels and decreased levels of anticoagulant proteins such as protein C. [21][22][23][24][25][26][27] graft versus host disease (GVHD) is associated with inflammation that leads to endothelial damage and activation. 28 TNF alpha, an essential mediator in the pathogenesis of GVHD, has been shown to enhance pro-thrombotic alterations on the endothelial cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cell injury was believed to be the responsible underlying lesion, causing various organ toxicities leading to a deficiency in various coagulation factors. 7 Factor VII deficiency may also be acquired in various conditions such as liver failure, anticoagulation administrations and vitamin K deficiency.…”
Section: Discussionmentioning
confidence: 99%